Cape Verde : Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper focuses on Cape Verde's Growth and Poverty Reduction Strategy Paper (DECRP). The Strategy of Growth and Poverty Reduction is an integral part of a strategic planning process. The institutional framework for the implementation of the DECRP is based on the existing administrative structures, incorporating such functional restructuring operations as are deemed appropriate. The final version of the DECRP will reflect enhanced coordination and a focus on policy consistency for those issues addressed in the preliminary version alongside other matters not dealt with in sufficient detail.